Stress during Commercial Hatchery Processing Induces Long-Time Negative Cognitive Judgement Bias in Chickens - Louise Hedlund; Tiphaine Palazon; Per Jensen (Animals, 2021)
Worldwide, billions of laying hen chicks are incubated and processed under highly industrialised circumstances every year, which, as we have previously shown, has long-lasting effects. Here, we measured corticosterone incorporated in down feathers to investigate possible stress during the incubation and showed that commercially incubated chicks did not have elevated levels of feather corticosterone, which implies that the main part of the stress effects from hatchery originates from the perinatal period and the handling immediately post-hatch. Further, we investigated how the early hatchery stress affects the chicks’ cognitive welfare state, i.e., “optimism” and “pessimism”. We exposed commercially hatched chickens to a positive cue, an aversive cue and ambiguous cues. The birds were tested at 1 and 10 w of age and the behaviour was compared with that of non-stressed chicks. Latencies to approach ambiguous cues were longer for the stressed chicks, both at 1 (p = 0.008) and at 10 (p = 0.020) weeks of age, i.e., these showed a more pessimistic-like behaviour. We conclude that the main part of the stress effects in commercially hatched chicks originates in the perinatal period, and further, that these birds show lasting levels of increased pessimism. This strongly indicates a long-time poorer welfare state for the animals.